A direct comparison of decision rules for early discharge of suspected acute coronary syndromes in the era of high sensitivity troponin. Issue 5 (August 2019) - Chew, Pei Gee; Frost, Fredrick; Mullen, Liam; Fisher, Michael; Zadeh, Heidar; Grainger, Ruth; Albouaini, Khaled; Dodd, James; Patel, Bilal; Velavan, Periaswamy; Kunadian, Babu; Rawat, Anju; et al.
Background: We tested the hypothesis that a single high sensitivity troponin at limits of detection (LOD HSTnT) (<5 ng/l) combined with a presentation non-ischaemic electrocardiogram is superior to low-risk Global Registry of Acute Coronary Events (GRACE) (<75), Thrombolysis in Myocardial Infarction (TIMI) (≤1) and History, ECG, Age, Risk factors and Troponin (HEART) score (≤3) as an aid to early, safe discharge for suspected acute coronary syndrome. Methods: In a prospective cohort study, risk scores were computed in consecutive patients with suspected acute coronary syndrome presenting to the Emergency Room of a large English hospital. Adjudication of myocardial infarction, as per third universal definition, involved a two-physician, blinded, independent review of all biomarker positive chest pain re-presentations to any national hospital. The primary and secondary outcome was a composite of type 1 myocardial infarction, unplanned coronary revascularisation and all cause death (MACE) at six weeks and one year. Results: Of 3054 consecutive presentations with chest pain 1642 had suspected acute coronary syndrome (52% male, median age 59 years, 14% diabetic, 20% previous myocardial infarction). Median time from chest pain to presentation was 9.7 h. Re-presentations occurred in eight hospitals with 100% follow-up achieved. Two hundred and eleven (12.9%) and 279 (17%) were adjudicated to suffer MACE at six weeks and one year respectively. Only HEART ≤3 (negative predictive value MACE 99.4%, sensitivity 97.6%, %discharge 53.4) and LOD HSTnT strategy (negative predictive value MACE 99.8%, sensitivity 99.5%, %discharge 36.9) achieved pre-specified negative predictive value of >99% for MACE at six weeks. For type 1 myocardial infarction alone the negative predictive values at six weeks and one year were identical, for both HEART ≤3 and LOD HSTnT at 99.8% and 99.5% respectively. Conclusion: HEART ≤3 or LOD HSTnT strategy rules out short and medium term myocardial infarction with ≥99.5% certainty, and short-term MACE with >99% certainty, allowing for early discharge of 53.4% and 36.9% respectively of suspected acute coronary syndrome. Adoption of either strategy has the potential to greatly reduce Emergency Room pressures and minimise follow-up investigations. Very early presenters (<3 h), due to limited numbers, are excluded from these conclusions.